41 Fostering Hope: The Comprehensive Accessible care for Infants with Neonatal abstinence (CAIN) Study. (19th August 2020) - Clarke, Denise; Hicks, Matt; Foss, Karen; Lifeso, Natasha
Abstract: Introduction/Background: Neonatal Abstinence Syndrome (NAS) occurs in newborns exposed to drugs in-utero. In Canada, maternal opiate use in pregnancy has been steadily rising resulting in as many as 1850 babies born with NAS per year. Management of babies born with NAS requires supportive, interdisciplinary care. Depending on the severity of NAS, babies may be cared for with non-pharmacological interventions or some may need to be admitted to the Neonatal Intensive Care Unit for extended hospital stays to receive medication and management of ongoing complex health care needs. Hospital and community health care providers have expressed concerns around the continuity of care for these babies in their stay in hospital and their transition to home. Objectives: This study examined the experiences of hospital and community-based health care providers and families regarding the management of babies with NAS. The driving force behind our inquiry related to our interest in streamlining care for these babies in highly complex health and social systems. Design/Methods: In total, 47 interdisciplinary participants were interviewed over a four-month period with individuals from Women's and Child Health, Community, and family members. Interviewed transcripts were reviewed over several months and were completed in December 2019 using an inductive thematic analysis which culminated in the identification of an overarching theme linked with primary themes. ​ Results: The study identified existing gaps in the management of these patients, determined how to improve communication between hospital and community networks, and provided a better understanding of the attitudes, perceptions and experiences of hospital and community personnel. The overarching theme identified was hope, with the primary themes being: system, mental health, mother/baby, judgement, and knowledge (see Figure 1). Several gaps identified in the system included fear, stigma, and language. Certain solutions proposed for improvement included focused care in a rooming in model for the mother and baby dyad, supporting mothers' well-being, involving mothers and families, and supporting care providers in a family centered care model. In Figure 1, green lines indicate themes that are linked with and support hope, and red lines indicate themes that are barriers to hope. Conclusion: This research demonstrates that programs and interventions implemented when working with mothers and babies with NAS must foster hope in mothers, families, and in the extended care provider team.